PERAN STRATEGI INTERVENSI SOSIAL DALAM PENDIDIKAN UNTUK MENGATASI KENAKALAN REMAJA - Eha Amelya Suherman; Sesya Surya Safira, Kayla Rahayu Putri, Aliffiah Novi Ramadhini, Tyo Hendryan, Tugimin Supriyadi (CV. ADIBA AISHA AMIRA, 2025)
Juvenile delinquency is a deviant behavior committed by adolescents, often violating social, ethical, or legal norms that apply. This phenomenon includes various actions such as brawls, skipping school, drug abuse, theft, or even violence. This phenomenon often occurs due to internal factors such as identity crisis and weak self-control, as well as external factors such as lack of parental attention and environmental influences. Social intervention strategies in education play an important role in overcoming juvenile delinquency, not only transferring knowledge but also shaping character, morals, and social values. The purpose of this study is to discuss the role of social intervention strategies in education to overcome juvenile delinquency. The method used in the preparation of this research is using Library research by using literature review. The results showed that education has an important role as an agent of social change. Eflective social intervention strategies involve collaboration between families, schools, and communities through measures such as group guidance, counseling, increased counseling services, and strengthening character education with a more positive attitude.